2013
DOI: 10.3109/08958378.2013.779767
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative damage and genotoxic effect in mice caused by sub-chronic exposure to low-dose volatile organic compounds

Abstract: Volatile organic compounds (VOCs) are widely used as constituents of household chemicals. Although adverse health effects have been reported, long-term exposure to low-level VOCs mixture has not been studied. Especially, there is a lack of substantial information on the sensitive biomarkers and carcinogenic markers. In the present study, we examined oxidative stress and genotoxic effects of sub-chronic low-dose VOCs mixture (formaldehyde, benzene, toluene and xylene). Male Kunming mice were exposed to 0 (contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 42 publications
1
25
1
Order By: Relevance
“…This result suggested that exposure to BTEX in air may increase the DNA damage in refueling workers, and the comet assay could be a useful detection method for occupational exposure to BTEX via inhalation. Besides, there are animal experiments suggesting that long-term VOC inhalation, including BTEX inhalation at low levels, can cause oxidative stress and a genotoxicity response in mice [34]. Results showed that exposure to BTEX (indoor air quality standard dose) results in oxidative lung damage, which is supported by significant changes in GSH and MDA.…”
Section: Discussionmentioning
confidence: 99%
“…This result suggested that exposure to BTEX in air may increase the DNA damage in refueling workers, and the comet assay could be a useful detection method for occupational exposure to BTEX via inhalation. Besides, there are animal experiments suggesting that long-term VOC inhalation, including BTEX inhalation at low levels, can cause oxidative stress and a genotoxicity response in mice [34]. Results showed that exposure to BTEX (indoor air quality standard dose) results in oxidative lung damage, which is supported by significant changes in GSH and MDA.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of such gaseous compounds can influence the biological response to inhaled aerosols (Wang et al, 2013b, Wang et al, 2013a, Ebersviller et al, 2012). In particular, exposure to VOCs is associated with adverse changes in the pulmonary and cardiovascular system, including inflammation and heart rate variability, as well as changes in gene expression (Song et al, 2013, Weichenthal et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Also, we excluded animal studies with mixtures where effects of FA could not be disentangled (e.g. Wang et al 2013a) and studies with exposures to FA aerosols (e.g. Lima et al 2015) as the WHO IAQG is set for gaseous FA.…”
Section: Introductionmentioning
confidence: 99%